Stakeholder engagement in prioritizing sustainability assessment themes for smallholder coffee production in Uganda - Ssebunya, B.R.; Schmid, Erwin; Asten, Piet J.A. van; Schader, C.; Altenbuchner, C.; Stolze, M. (Cambridge University Press, 2017)
Many sustainability assessment frameworks have been developed in recent years, but translating them into practical tools to guide decision making remains challenging. By engaging coffee stakeholders in Uganda, we demonstrate a process of translating the widely-accepted framework for Sustainability Assessments of Food and Agriculture Systems (SAFA), developed by the Food and Agriculture Organisation of the United Nations (FAO), to smallholder production systems. Stakeholders prioritized the sustainability themes in terms of relevance and feasibility, and subsequently identified relevant sub-themes. We find that the structure and scope of some generally accepted themes need appropriate modifications in order to address the social and structural heterogeneity of smallholder production systems. Although importance and feasibility rankings significantly vary within and between stakeholder groups, governance and economic themes are commonly perceived as very important though equally the least feasible for smallholders. Thus, the inclusion of the ‘farmer-group’ structure as part of the sustainability assessment criteria is perceived as necessary especially toward achieving governance-related goals. These findings emphasize the need of engaging stakeholders in defining locally adapted sustainability assessment criteria.